Production and Application of Carbon Dots from Sugarcane Bagasse-Derived-Lignin for Pb2+ Ion Detection - Berlian Sitorus; Dionisius Rio; Intan Syahbanu; Seno Darmawan Panjaitan (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2025)
This study investigates the formation and application of carbon dots derived from sugarcane bagasse lignin for lead ion detection. Lignin was extracted from bagasse using an alkaline treatment followed by precipitation with sulfuric acid. The isolated lignin was converted into carbon dots through a hydrothermal process. Characterization revealed a 7 ± 4 nm particle size distribution and distinctive absorbance peaks at 236, 317, and 360 nm in UV-Vis spectroscopy. To test their application in lead detection, the carbon dots are exposed to Pb2+ ions in concentrations of 0.01, 0.1, 1, and 10 µM. The carbon dots exhibited a notable fluorescence quenching response in the presence of Pb2+ ions. Photoluminescence spectroscopy confirmed that lead ions interact with the carbon dots, reducing their emission intensity. These findings demonstrate the potential of lignin-derived carbon dots as effective sensors for Pb2+ ion detection.